Isolation and Measurement of Respiration and Structural Studies of Purified Mitochondria from Heterotrophic Plant Tissues. Issue 12 (17th December 2021) - Pandey, Sonika; Kumari, Aprajita; Singh, Pooja; Gupta, Kapuganti Jagadis
Abstract: Mitochondria are the power houses of eukaryotic cells. These organelles contain various oxidoreductase complexes. Electron transfer from different reducing equivalents channeled via these complexes drives proton translocation across the inner mitochondrial membrane, leading to ATP generation. Plant mitochondria contain alternative NAD(P)H dehydrogenases, alternative oxidase, and uncoupling protein, and TCA cycle enzymes are located in their matrix. Apart from ATP production, mitochondria are also involved in synthesis of vitamins and cofactors and participate in fatty acid, nucleotide, photorespiratory, and antioxidant metabolism. Recent emerging evidence suggests that mitochondria play a role in redox signaling and generation of reactive oxygen and nitrogen species. For mitochondrial studies, it is essential to isolate physiologically active mitochondria with good structural integrity. In this article, we explain a detailed procedure for isolation of mitochondria from various heterotrophic tissues, such as germinating chickpea seeds, potato tubers, and cauliflower florets. This procedure requires discontinuous Percoll gradient centrifugation and can give a good yield of mitochondria, in the range of 4 to 8 mg per 50 g tissue with active respiratory capacity. After MitoTracker staining, isolated mitochondria can be visualized by using a confocal microscope. The structure of mitochondria can be monitored by scanning electron microscopy. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Isolation of mitochondria from germinating chickpea seeds, potato tubers, and cauliflower florets Basic Protocol 2 : Quantification of mitochondrial protein concentration by Bradford assay Basic Protocol 3 : Quantification of mitochondrial respiration using single‐channel free‐radical analyzer Basic Protocol 4 : Staining of mitochondria and confocal imaging Basic Protocol 5 : Visualization of isolated mitochondria under scanning electron microscope